Improvement of Hygienic and Phytochemical Qualities of Mangosteen (Garcinia Mangostana) Peel by Irradiation - Eamsiri, Jaruratana; Pewlong, Wachiraporn; Sajjabut, Surasak; Chookaew, Sirilak; Khemtong, Khemruji; Photinam, Ratchaneeporn; Prakongsil, Punchalee (Trends in Sciences, 2024)
The aim of this study was to compare the effects of gamma ray and x-ray irradiation at different dose levels 95, 10, 15 and 20 kGy) on in mangosteen peel. The antioxidant activities were assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP), while total phenolic contents and antibacterial activities against Staphylococcus aureus and Escherichia coli of 60 % ethanolic mangosteen powder extracts were analyzed. The results indicated that both types of ionizing radiations showed a non-significant decrease in measured parameters with increasing doses. The minimum inhibitory concentration (MIC) values of irradiated mangosteen peel extracted against S. aureus and E. coli ranged from 0.125 to 2.0 mg/mL. The quantity of bioactive compound mangostin determined via high-performance liquid chromatography (HPLC), did not show significant decrease with different irradiation sources and doses. In microbiological aspect, total yeast and mold from both irradiation sources were reduced by 1 log cycle after irradiation at 5 kGy. The irradiation induced color changes corresponding to Hunter color L a b value. X-ray irradiation caused slight color alteration compared to gamma rays. The advantage of x-ray irradiation was that it revealed non-significant changes in b values, whereas gamma irradiation showed the significant change in L, and b values with increasing dosage. The x-ray irradiation at the dose 5 kGy effectively decreased microbial contamination while causing minimal changes to phytochemical qualities and color. HIGHLIGHTS Irradiation at 5 kGy was sufficient to control microbial contamination There were no significant changes in antioxidant activities (DPPH, FRAP), a-mangostin contents, total phenolic contents (TPC) and antibacterial activities: after irradiation up to 20 kGy X-ray irradiation was an excellent alternative to gamma irradiation for decontamination with a non-significant alteration in b values. GRAPHICAL ABSTRACT